2018
DOI: 10.3892/mmr.2018.8860
|View full text |Cite
|
Sign up to set email alerts
|

Role of cantharidin in the activation of IKKα/IκBα/NF‑κB pathway by inhibiting PP2A activity in cholangiocarcinoma cell lines

Abstract: Cantharidin (CAN), a potent inhibitor of serine/threonine-protein phosphatase 2A (PP2A), is widely used in clinical practice, particularly in the treatment of advanced cancer due to its specific action on these types of cancer. In the present study, the inhibitory effect of CAN was examined in two cholangiocarcinoma cell lines (QBC939 and Hucc-t1). Following treatment with CAN, cell viability was effectively reduced in QBC939 and Hucc-t1 cells and normal human intrahepatic biliary epithelial cells. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Moreover, cantharidin has been shown to increase the level of Bax, inhibit the level of Bcl-2 and survivin expression (Zhang et al, 2005), subsequently resulting in apoptotic cell death (Bonness et al, 2006). Particularly, cantharidin inhibits cancer cell migration and invasion via activating the IKKα/IκBα/NF-κB pathway by inhibiting PP2A activity (Zhou et al, 2018) or suppressing the MMPs (Ji et al, 2015; Shen et al, 2015), suggesting it may be a potential anti-metastatic compound. However, its anti-metastatic mechanism is far less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cantharidin has been shown to increase the level of Bax, inhibit the level of Bcl-2 and survivin expression (Zhang et al, 2005), subsequently resulting in apoptotic cell death (Bonness et al, 2006). Particularly, cantharidin inhibits cancer cell migration and invasion via activating the IKKα/IκBα/NF-κB pathway by inhibiting PP2A activity (Zhou et al, 2018) or suppressing the MMPs (Ji et al, 2015; Shen et al, 2015), suggesting it may be a potential anti-metastatic compound. However, its anti-metastatic mechanism is far less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Given that p-ERK is the main target of sorafenib and that MLN4924 did not have any effect on p-ERK levels, this suggests that ERK was not involved in MLN4924-mediated sorafinib sensitization. A previous study reported that MMP9, a downstream target of NF-κB, was important for regulating cell migration (30). However, we found that MMP9 was not associated with sorafineb sensitization triggered by MLN4924 in HCC cells, as indicated by no significant changes to MMP9 levels in the presence or absence of MLN4924.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway analysis results demonstrated seven signaling pathways closely related to HCC treatment, involving phenylalanine, tyrosine and tryptophan biosynthesis, d ‐glutamine and d ‐glutamate metabolism, alanine, aspartate and glutamate metabolism, phenylalanine metabolism, arginine biosynthesis, the TCA cycle, and purine metabolism. Among them, cantharidin can affect the expression of related enzymes involved in the TCA cycle by regulating the NF‐ κ B pathway (Todisco et al, 2019; Yang, Zhang, et al, 2021; Zhou et al, 2018). Ginsenosides Rg1 and Rd can block the de novo purine biosynthetic pathway by inhibiting the PI3K/AKT/mTOR pathway (Li et al, 2019; Pedley & Benkovic, 2017; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%